2007
DOI: 10.1891/088667007781553964
|View full text |Cite
|
Sign up to set email alerts
|

The Control Motive and Marital Violence

Abstract: The role of the control motive in marital violence is examined using data on current and former marriages from the Survey of Violence and Threats of Violence Against Women and Men. The findings indicate no support for the position that husbands engage in more marital violence than wives because they are more controlling. In former marriages, we observe statistical interactions between gender and control: former husbands who were controlling or jealous were particularly likely to be verbally aggressive and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 0 publications
3
76
0
4
Order By: Relevance
“…Large-scale national surveys conducted in the United States and have measured the extent of CCV in the general population (Felson & Outlaw, 2007;Jasinski, Blumenstein, & Morgan, 2014;Laroche, 2005). The latest of these surveys identified 36% of female IPV victims to have experienced CCV compared to 35% of male victims.…”
Section: Differential Treatmentmentioning
confidence: 99%
“…Large-scale national surveys conducted in the United States and have measured the extent of CCV in the general population (Felson & Outlaw, 2007;Jasinski, Blumenstein, & Morgan, 2014;Laroche, 2005). The latest of these surveys identified 36% of female IPV victims to have experienced CCV compared to 35% of male victims.…”
Section: Differential Treatmentmentioning
confidence: 99%
“…For example, in an empirical study by Graham-Kevan and Archer (2008) of shelter residents, male and female students, and male prisoners, control accounted for significant proportions of the variance in the use of physical aggression for many other subtypes of perpetrators, including those thought to be perpetrating situational couple violence. Similarly, using data from the National Violence Against Women Survey (NVAWS), Felson and Outlaw (2007) concluded that husbands and wives differ mostly in the types of controlling behaviors they are engaged in, rather than in their overall amount of controlling behavior. The extent to which researchers and clinicians may have to be able to reliably differentiate control as a situation-specific motivation for violence as opposed to control as a general and underlying relationship pattern in order to determine subtype membership awaits continued study.…”
Section: Challenge #2mentioning
confidence: 99%
“…Bates and GrahamKevan (2012) found that men and women were equally likely to be categorized as intimate terrorists. Other studies indicate that control and controlling aggression are characteristic of both sexes (Dutton & Nicholls, 2005;Felson & Outlaw, 2007;Graham-Kevan, 2007;GrahamKevan & Archer, 2009). Furthermore, Hines (e.g., Hines & Saudino, 2003;Hines, Brown, & Dunning, 2007;Hines & Douglas, 2010) has described the severe physical and psychological effects that male victims of IPV suffer.…”
Section: Introductionmentioning
confidence: 98%